Between-domain relations of students' academic emotions and their judgments of school domain similarity - Goetz, Thomas; Haag, Ludwig; Lipnevich, Anastasiya A.; Keller, Melanie M.; Frenzel, Anne C.; Collier, Antonie P. M. (Frontiers in Psychology, 2014)
With the aim to deepen our understanding of the between-domain relations of academic emotions, a series of three studies was conducted. We theorized that between-domain relations of trait (i.e., habitual) emotions reflected students’ judgments of domain similarities, whereas between-domain relations of state (i.e., momentary) emotions did not. This supposition was based on the accessibility model of emotional self-report, according to which individuals’ beliefs tend to strongly impact trait, but not state emotions. The aim of Study 1 (interviews; N = 40; 8th and 11th graders) was to gather salient characteristics of academic domains from students’ perspective. In Study 2 (N=1709; 8th and 11th graders) the 13 characteristics identified in Study 1 were assessed along with academic emotions in four different domains (mathematics, physics, German, and English) using a questionnaire-based trait assessment. With respect to the same domains, state emotions were assessed in Study 3 (N = 121; 8th and 11th graders) by employing an experience sampling approach. In line with our initial assumptions, between-domain relations of trait but not state academic emotions reflected between-domain relations of domain characteristics. Implications for research and practice are discussed.